Anatonia de raízes, folhas e escapos de espécies de Paepalanthus subgênero Platycaulon (Eriocaulaceae) - Scatena, Vera Lucia [UNESP]; De Moraes, Ana Rosa Soares (My University, 1996)
The anatomical features of roots, leaves and scapes of the subgenus Platycaulon, genus Paepalanthus (Eriocaulaceae) that grow in the Brasilian rupestrian fields of Serra do Cipó - MG - Brazil were studied. The following main anatomical features were found: epidermis cells of varied thicknesses, chlorenchyma with compact or spread organization and leaf margin shape in the leaves; the scapes with continuous or discontinuous endodermis, divided or undivided pericycle, vascular bundles absent in the cortex and in the pith. These anatomical characteristics of the leaves and scapes occur in different species and can be used to separate them into Divise or Conferti sections. It was possible to confirm the proposed taxonomy based only on the morphological characteristics. Other anatomical features such as: presence or absence of air in the cortex roots and hypodermis which originate water parenchyma reserves in the mesophyll, can be an adaptative response that plants towards produce the environmental factors in this ecosystem.
Roots, leaves and scapes anatomy of species of Paepalanthus subgenus Platycaulon (Eriocaulaceae)
Keywords: Adaptation; Leaves and scapes anatomy; Paepalanthus; Roots; Taxonomy